Validation of educational booklet for HIV/Aids prevention in older adults - Luana Ibiapina Cordeiro; Thais de Oliveira Lopes; Luciane Elise de Abreu Lira; Sarah Maria de Sousa Feitoza; Maria Eliana Peixoto Bessa; Maria Lúcia Duarte Pereira; Aline Rodrigues Feitoza; Adriano Rodrigues de Souza
ABSTRACT Objective: To describe the process of manufacturing and validation of an educational booklet for HIV/Aids prevention in older adults Methods: Methodological study developed in two phases - manufacturing of the booklet and validation of the educational material by judges. The manufacturing process involved a situational diagnosis with older adults, and its result indicated gaps in the knowledge with respect to HIV/Aids. The validation process was performed by nine judges, selected by convenience. It was considered an agreement index of at least 0.80, analyzed through the content validity index. Results: We opted for a dialogue between two older adults divided into three categories: myths and taboos; ignorance; and prevention and importance of diagnosis. The average of the items was 0.90. The suggestions made by the judges were observed and modified for the final version. Conclusion: The material had relevant content for the judges, in addition to being able to be used by health professionals in the education and clarification of issues on the subject.